(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
The article describes the importance, essence and scientific and theoretical foundations of the development of the dairy cattle breeding industry. As a result of the conducted scientific research, a system of theoretical approaches was developed based on the study of the scientific works of foreign and domestic economists in order to study the economic efficiency of milk production in the cattle breeding industry.